2007
DOI: 10.1007/s00423-007-0205-2
|View full text |Cite
|
Sign up to set email alerts
|

Poor late prognosis of bleeding peptic ulcer

Abstract: Long-term prognosis of peptic ulcer bleeding is poor! The majority of deaths after hospital stay is probably not because of ulcer bleeding, but because of more aged patients with severe concomitant diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
2
4
1
Order By: Relevance
“…In accordance with previous studies [2][3][4][5][6][7][8], we observed that the long-term mortality was higher in PUB patients than in an age-and sex-matched control cohorts. Unfortunately, it is not possible to establish a well-defined focus area to mitigate the high long-term mortality in PUB patients.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In accordance with previous studies [2][3][4][5][6][7][8], we observed that the long-term mortality was higher in PUB patients than in an age-and sex-matched control cohorts. Unfortunately, it is not possible to establish a well-defined focus area to mitigate the high long-term mortality in PUB patients.…”
Section: Discussionsupporting
confidence: 94%
“…For reasons that are not fully understood, PUB is also associated with an excess long-term mortality, lasting many years after the bleeding episode has been managed [2][3][4][5][6][7][8]. The cause of long-term mortality in patients surviving an episode with PUB seems to be competing diseases as cancer, cardiovascular, or respiratory diseases, rather than recurrence of PUB [3,[5][6][7]9].…”
Section: Introductionmentioning
confidence: 99%
“…tables 5 and 6) [12,15,39,46,51,59,60,61,62,63,64,65,66,67]. In most cases, this increase in mortality was associated with age over 60 years.…”
Section: Resultsmentioning
confidence: 99%
“…Chronic liver disease increases the risk of peptic ulcer bleeding, a serious and frequent medical emergency with reported incidence ranging from 0.47 to 0.57 per 1000 person‐years . Despite improvements in peri‐operative management, post‐operative care, and adjuvant pharmacological treatment, mortality rates remain elevated, with reported 30‐day mortality as high as 12% …”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Despite improvements in peri-operative management, post-operative care, and adjuvant pharmacological treatment, mortality rates remain elevated, with reported 30-day mortality as high as 12%. [8][9][10][11][12][13] Comorbidity may contribute to mortality from peptic ulcer bleeding. 12,[14][15][16][17] In particular, liver disease may result in disturbances in coagulation and susceptibility to hypovolaemic shock and infection.…”
Section: Introductionmentioning
confidence: 99%